Powerglove: Genesis of a wearable technology aimed at studying volleyball service - Di Tore, P. A.; Raiola, G. (Journal of Human Sport & Exercise, 2019)
The spread, in sport, of technologies able to detect and organize in real time a wide range of data related to the athlete and the context (tracker, gps, gyroscopes, accelerometers, bio-sensors embedded in smartphones or available as wearable devices) offers a great opportunity to collect performance data, allowing objective, accurate and non-invasive physical activity monitoring. In particular, this type of detection allows to avoid all the interferences connected to the laboratory settings. Wearable devices using textiles with embedded physiological sensors are used in various applications involving monitoring, control and learning» (Helmer et al., 2010). In sport, wearable technologies allow detections that do not alter the "natural" scenario of the performance. This work presents the design and development of a wearable device for the collection of data relating to a fundamental of volleyball: the service. The device consists of a glove, wearable by the athlete, equipped with various ultra-thin sensors (such as not to affect performance). The sensors are operated by an Arduino Nano microcontroller, worn at the forearm level by an arm band. The basic sensor is a flexible and ultra-thin TekScan pressure sensor (<0.1 mm), able to detect the pressure exerted by the hand on the ball in a range between 0 and 100 kg with an accuracy of 100g and a sampling frequency of 100 Hz. Collected data are processed by a specially developed support software that provides elementary statistics and specific graphical representations and can be exported in the most common formats.